METHODS OF TEACHING VOCABULARY, PRONUNCIATION AND GRAMMAR SKILLS FOR PRE-SCHOOL CHILDREN - Sh. Mo'ydinova; Alaydinova Maharramxon (TADQIQOTLAR, 2025)
ANNOTATION: In order to have a good education, the teaching system of pre- school kids should improve positively. And this article looks at devices for teaching language skills including: vocabulary, pronunciation, listening and grammar. Also it gives methods and games with detailed information on the theme.